Evaluating Ammonia's Flammability and Explosion Hazards in Air and Oxygen at Elevated Conditions: Data Generation and Review According to the New European Standard - Benoit Tribouilloy; Esteban Paillery; Roberto Palomino; Alexis Vignes (Chemical Engineering Transactions)
Many industrial processes operate under non-atmospheric conditions, involving high pressure and temperature in a variety of oxidising media. It is therefore essential to assess the potential for explosive atmospheres of (vapour)/oxidising gases under these conditions. Explosive limits depend on pressure, temperature and the oxidising environment, and are determined using a variety of methods. To standardise these practices, the European standardisation committee CEN TC 305 has introduced a new method in 2022. The candidate for this study was ammonia, a promising carbon-free energy carrier (green ammonia) with a low environmental impact but which also presents challenges related to its manufacture and use. However, data on the flammability and explosibility of ammonia is limited, particularly under non-atmospheric conditions. A review of these data is presented in this document. The experimental part of this work aims to produce new data on the explosive limits of ammonia and the explosion severity according to this new standard in oxygen at an initial pressure of 0.5 MPa and at 200 °C. The main conclusions are as follows (1) the lower explosive limit remains around 10%vol, as proposed by Doring (1931), (2) the upper explosive limit reaches 93%vol under the conditions tested, (3) the maximum explosion pressure measured is 42 MPa (explosion ratio of 8.3), and (4) the maximum rate of pressure rise is 920 MPa.s-1. The application of the EN 17624 standardised method makes it possible to generate new, up-to-date data to improve our understanding of the safety limits of ammonia.